2014
DOI: 10.1097/gox.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Women’s Preferences and Preference Modeling for Breast Reconstruction Decision Making

Abstract: Background:Women considering breast reconstruction must make challenging trade-offs among issues that often conflict. It may be useful to quantify possible outcomes using a single summary measure to aid a breast cancer patient in choosing a form of breast reconstruction.Methods:In this study, we used multiattribute utility theory to combine multiple objectives to yield a summary value using 9 different preference models. We elicited the preferences of 36 women, aged 32 or older with no history of breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…Large-scale studies such as those highlighted above will continue to produce generalizable PROs that clinicians and patients can utilize in future decision making. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Large-scale studies such as those highlighted above will continue to produce generalizable PROs that clinicians and patients can utilize in future decision making. 30 …”
Section: Discussionmentioning
confidence: 99%
“…33 Second, beneficial appearance expectations and positive psychosocial expectations including the desire to feel normal and feminine, the expectation of improved quality of life, and wanting to “move on,” are cited as common reasons for choosing BR, 17,25,3436 and fear of complications and anxiety are cited as reasons not to choose BR. 25 However, with few exceptions, 37 research has used qualitative methods or assessed effects of BR on patient-reported outcomes after surgery, rather than a standardized assessment to evaluate reasons for choosing or not choosing BR. Third, other factors that contribute to decisions, such as satisfaction with preparation for the decision and decisional conflict, have not been examined during the time period when women are making the decision using standard instruments.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of candidate multiattribute utility functions (MAUFs) that may be used. We have shown that they perform equally well [36]. Let us assume that the additive MAUF is consistent with Jenn’s preferences.…”
Section: The Breast Reconstruction Decision: a Fictional Case Studymentioning
confidence: 99%